On security issues in embedded systems: challenges and solutions. (2nd June 2008) - Khelladi, Lyes; Challal, Yacine; Bouabdallah, Abdelmadjid; Badache, Nadjib
Ensuring security in embedded systems translates into several design challenges, imposed by the unique features of these systems. These features make the integration of conventional security mechanisms impractical, and require a better understanding of the whole security problem. This paper provides a unified view on security in embedded systems, by introducing first the implied design and architectural challenges. It then surveys and discusses the currently proposed security solutions that address these challenges, drawing from both current practices and emerging research, and identifies some open research problems that represent the most interesting areas of contribution.